1979
DOI: 10.1073/pnas.76.8.3819
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the NH2-terminal extra piece of the precursor to human placental lactogen.

Abstract: The cell-free translation product of human placental lactogen mRNA is a precursor molecule larger than the mature hormone that circulates in plasma. To determine the structure of pre-placental lactogen, the poly(A)-rich RNA fraction of term placenta was isolated and translated in a wheat germ cell-free system. The mRNA programmed the synthesis of a major protein, 3000 daltons larger than placental lactogen, that was specifically precipitated by hormone antibodies. The immunoprecipitated protein was labeled sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…These fragments were compatible with the published DNA sequence (10,11) and suggested that our clone included the entire coding region for preproPTH. (10) showing cell-free translation products of poly (A)-rich RNA in a wheat germ system (6) (Fig. 4) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These fragments were compatible with the published DNA sequence (10,11) and suggested that our clone included the entire coding region for preproPTH. (10) showing cell-free translation products of poly (A)-rich RNA in a wheat germ system (6) (Fig. 4) …”
Section: Resultsmentioning
confidence: 99%
“…1, left) (6). When pPTH10 was immobilized on nitrocellulose, hybridized to total RNA under stringent conditions, and boiled, only mRNA translating pre-proPTH was identified (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In eucaryotes, the extent of removal of the initiating methionine in vivo varies depending on which amino acids occur in the penultimate and subpenultimate positions (427). When translation is carried out in vitro with extracts from eucaryotic cells, the NH2-terminal methionine is sometimes removed from the growing polypeptide (190,201,272,282,345) and sometimes not (36,344,384,428). The vast majority of eucaryotic proteins are blocked by post-translational acetylation of the (original or derived) terminal a-NH2 group (36,54) or by some alternative blocking group (532).…”
Section: Soluble Protein Factors Required For Initiationmentioning
confidence: 99%
“…As the efficiency of the first-trimester and term mRNA is similar in terms of amino acid incorporation, it would appear that the relative levels of hPL mRNA are greater in the term placenta (Boime et al, 1976). When free polysomes are used in a cell-free system a 'pre-lactogen' of molecular weight 25 000 is produced; the extra protein or 'precursor piece' is at the N-terminus of the molecule and contains an abundance of leucine residues (Birken et al, 1977;Sherwood et al, 1979). In the presence of membrane fractions from endoplasmic reticulum, the 'prelactogen' is converted to authentic hPL; this 'precursor piece' (Figure 5.6) is a 25 amino acid sequence which may play a part in the formation of membrane-bound ribosomal complexes (Blobel and Dobberstein, 1975) (Figure 5.7).…”
Section: Biosynthesis (A) Source Of Hplmentioning
confidence: 99%